Identification of surfactin as an anti-severe fever with thrombocytopenia syndrome virus multi-target compound extracted from the culture broth of marine microbes - Urata, Shuzo; Takouda, Jun; Watanabe, Yoshihiro; Sakaguchi, Miako; Sakurai, Yasuteru; Inahashi, Yuki; Iwatsuki, Masato; Yasuda, Jiro; Tanaka, Yoshimasa; Takeda, Kohsuke (Frontiers in Virology, 2023)
Severe fever with thrombocytopenia syndrome virus (SFTSV) is a tick-borne virus first identified in China in 2011 and later reported in other Asian countries. Significant efforts have been made to develop anti-SFTSV compounds; however, there are no approved vaccines or antivirals against SFTSV infections. Marine organisms provide nearly unlimited biological resources to produce therapeutic drugs for the treatment and control of disease. In this study, we aimed to identify anti-SFTSV chemical compounds from the culture broth extracts of marine microbes collected from the coasts of the Nagasaki Prefecture, Japan. Of the 80 extracts, two showed an anti-SFTSV effect. One of them, which exhibited low cell toxicity, was used for further characterization. Chemical analysis combined with the anti-SFTSV effect identified surfactin as one of the main components of the selected extract. Our study showed a proof-of-concept to identify novel antiviral compounds from marine microbes against the virus of interest. Further analysis showed that surfactin affected the integrity of the virion membrane and inhibited SFTSV infection-induced membrane fusion at low pH conditions. Furthermore, surfactin inhibits the post-entry step of viral replication in the cell, which is a novel mode of antiviral action of surfactin. These results indicate that surfactin can target multiple steps of SFTSV replication in cells.